2016
DOI: 10.1096/fj.201600609r
|View full text |Cite
|
Sign up to set email alerts
|

Lipid rafts of mouse liver contain nonextended and extended acetylcholinesterase variants along with M3 muscarinic receptors

Abstract: The observation of acetylcholinesterase (AChE) type H (AChE), which is the predominant AChE variant in visceral organs and immune cells, in lipid rafts of muscle supports functional reasons for the raft targeting of glypiated AChE The search for these reasons revealed that liver AChE activity is mostly confined to rafts and that the liver is able to make N-extended AChE variants and target them to rafts. These results prompted us to test whether AChE and muscarinic receptors existed in the same raft. Isolation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…AChE mainly resides in synaptic cleft, but the pool of AChE is located in association with lipid rafts through a GPI anchor [82]. Close distribution of raft-linked AChE to plasma membrane enriched with the receptors (e.g., M3 muscarinic receptors) could be important for control local levels of ACh near the receptors [83]. Accordingly, presence of cholesterol-rich microdomains may control sensitivity of feedback mechanisms which regulate ACh release from nerve terminals.…”
Section: Cholesterol and Proteins Involved In Synaptic Vesicle Cyclementioning
confidence: 99%
“…AChE mainly resides in synaptic cleft, but the pool of AChE is located in association with lipid rafts through a GPI anchor [82]. Close distribution of raft-linked AChE to plasma membrane enriched with the receptors (e.g., M3 muscarinic receptors) could be important for control local levels of ACh near the receptors [83]. Accordingly, presence of cholesterol-rich microdomains may control sensitivity of feedback mechanisms which regulate ACh release from nerve terminals.…”
Section: Cholesterol and Proteins Involved In Synaptic Vesicle Cyclementioning
confidence: 99%
“…Therefore, to determine if the decrease in ovarian ACh levels is mediated by an increase in AChE, we analyzed its levels by western blot. In this sense, while AChE-R has a size of approximately 55 kDa ( 33 35 ), AChE-S has several posttranslational modifications, and its size could be 70, 60, and even 55 kDa ( 33 36 ). Figure 2 shows the western blot analysis results for AChE, and we found two main bands at 70 kDa and 55 kD ( Figure 2A ).…”
Section: Resultsmentioning
confidence: 99%
“…In studies involving mice and humans, AChE-S has shown different molecular weights (55, 60, and 70 kDa) depending on posttranslational modifications ( 33 36 ). The molecular size of AChE-R was found to be 55 kDa in studies involving mice and humans ( 33 35 ). When we analyzed AChE by western blotting after NGF stimulation and found a 2-fold increase only in the 55 kDa-isoform.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation